Experience of clinical incivility and stress in nursing students: A mixed-method study - Youngjin Lee; Cheryl Brandt; Younglee Kim (PLoS ONE, 2025)
Nursing students often experience uncivil words or actions during clinical practice which can lead to significant stress. The purpose of our study was to quantitatively investigate the degree of clinical incivility and stress experienced by students and the statistical relationship between them and qualitatively explore students’ personal experiences of clinical incivility and stress. Our study was conducted from April 25 to May 27, 2023, using a mixed-method design. Phase One, the quantitative component, used a non-experimental, descriptive, cross-sectional study design with a 10-minute self-administered online survey. Phase Two, the qualitative component, used an in-person focus group to collect data on participants’ personal experiences of clinical incivility and stress. A total of 159 junior and senior pre-licensure nursing students attending a clinical practicum of a Bachelor of Science in Nursing (BSN) program in South Korea completed the quantitative online survey. Subsequently, 20 students voluntarily attended focus group sessions. To analyze the online survey data the study sample was divided into a clinical incivility group and a non-clinical incivility group. A group comparative analysis using chi-square and t-test was conducted. To analyze the qualitative focus group data, Colaizzi’s method to identify significant themes was used. Prevalence of clinical incivility experience in the students was 79.9% (n = 123 out of 159). Clinical incivility was significantly positively correlated with the students’ reported stress level (r = .317, p < .001); students who experienced greater clinical incivility reported higher levels of stress. Additionally, higher levels of clinical incivility were linked to lower levels of satisfaction with clinical practice and the clinical site. Analysis of the focus group data revealed four main themes regarding the students’ experiences: 1) Being defenselessly exposed to verbal or nonverbal abuse, 2) Not being treated as a student nurse, 3) Experiencing a combination of negative feelings, and 4) Taking incivility for granted in the clinical site. Major perpetrators of clinical incivility among nursing students were nurses at the clinical sites. To prevent and manage clinical incivility, nursing schools and clinical agencies must collaborate to establish incivility monitoring, communication, and evidence-based policies and intervention programs.